International adoption: Symptoms of attachment disorders and their associations with the child’s background and developmental outcome - Raaska, Hanna (Annales Universitatis Turkuensis D 1195, 2015)
Many internationally adopted children have lived their first years of life in an environment with limited opportunities for primary caregiving. The lack of consistent care increases the prevalence of attachment disorders among them. Less is known about the influences of attachment disorders on a child’s later course of life. This study is part of the Finnish Adoption Study. Parents of all Finnish children who had been internationally adopted by legal adoption organisations between 1985 and 2007 were sent questionnaires (N=1450). Parental evaluations of the children’s symptoms of reactive attachment disorder (RAD) at the time of adoption, their later learning or language problems using a screening scale, and children’s self-reported school bullying experiences were evaluated. Each child’s attachment-related behavioural problems were requested in a follow-up survey 1.9 and 3.8 years after adoption and compared with a Finnish reference group. This study indicated that Finnish internationally adopted children have at least three-fold prevalence of learning and language problems compared with their age-mates. A child’s symptoms of attachment disorders were associated with learning or language problems at school age as well as with his/her school bullying experiences. The adopted children had more attachment-related behavioural problems two years after adoption than their age-mates, but the difference was no longer evident four years after adoption. In conclusion, this study showed that the symptoms of attachment disorder indicate a risk for an adopted child’s later developmental outcome. The findings demonstrate the need for comprehensive clinical examinations and planning of treatment strategies for children with symptoms of RAD.

Monet ulkomailta adoptoidut lapset ovat eläneet ensimmäisen elinvuotensa ympäristössä, jossa ei ole ollut mahdollisuutta muodostaa suhdetta yhteen pääasiallisesti lasta hoivaavaan aikuiseen. Pysyvän hoivaajasuhteen puutteen tiedetään lisäävän kiintymyssuhdehäiriöiden esiintyvyyttä. Vähemmän kuitenkin tiedetään näiden häiriöiden vaikutuksista lapsen myöhempään kehitykseen. Tämä tutkimus on osa suomalaista FinAdo- tutkimusta (Finnish Adoption Study). Tutkimuksessa lähetettiin kyselylomakkeita kaikille vuosina 1985-2007 adoptiojärjestöjen kautta adoptoitujen lasten vanhemmille ja lapsille itselleen (N= 1450). Vanhemmat arvioivat lapsen reaktiivisen kiintymyssuhdehäiriön oireita adoption jälkeen, lapsen senhetkisiä oppimiseen ja kielenkehitykseen liittyviä ongelmia, sekä lapsilta itseltään kysyttiin heidän koulukiusauskokemuksistaan. Tämän lisäksi arvioitiin muutosta osalle lapsista toteutettavassa kiintymyssuhdekäyttäytymisen seurantatutkimuksessa 1,9 ja 3,8 vuotta adoption jälkeen. Tuloksia verrattiin suomalaiseen verrokkiryhmään. Tutkimus osoittaa, että suomalaisilla adoptiolapsilla on vähintään kolme kertaa enemmän oppimisen ja kielenkehityksen ongelmia kuin heidän ikätovereillaan. Oppimisen ja kielenkehityksen ongelmia sekä koulukiusauskokemuksia oli enemmän niillä lapsilla joilla oli tulovaiheessa kiintymyssuhdehäiriön oireita. Adoptoiduilla lapsilla oli enemmän kiintymyssuhdekäytöksen ongelmia kuin verrokkilapsilla kaksi vuotta adoption jälkeen, mutta ero ikätovereihin ei ollut nähtävissä enää neljä vuotta adoptiosta. Tutkimuksen johtopäätöksenä voidaan todeta, että adoption jälkeiset kiintymyssuhdehäiriön oireet ovat merkki riskistä myöhemmille kehityksen ongelmille. Tutkimus osoittaa laaja-alaisen kehityksellisen arvion ja hoitosuunnitelman tarpeellisuuden mikäli lapsella on näitä oireita.